If it's not what You are looking for type in the equation solver your own equation and let us solve it.
(5x-3)(4x+9)=0
We multiply parentheses ..
(+20x^2+45x-12x-27)=0
We get rid of parentheses
20x^2+45x-12x-27=0
We add all the numbers together, and all the variables
20x^2+33x-27=0
a = 20; b = 33; c = -27;
Δ = b2-4ac
Δ = 332-4·20·(-27)
Δ = 3249
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$$\sqrt{\Delta}=\sqrt{3249}=57$$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(33)-57}{2*20}=\frac{-90}{40} =-2+1/4 $$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(33)+57}{2*20}=\frac{24}{40} =3/5 $
| -30=26-8.9x | | 756/(401-x)=6 | | 1+7(-3a+5)=183 | | 15=-3(2x+1) | | 4c+9=c | | 10-6m=-9-9m-2 | | 3(x-7)=4x-8 | | -95=-4-7(x+5) | | 30=10c-5c | | n^2−5n−2=0 | | -2.6b+4=0.9b–17. | | -4-9p=2-10p | | 7x(x-5)=-12 | | u+6/6=3 | | 85=1.8x-80 | | -10+5p=6-6+3p | | 4t^2+11t+2=4t | | -2z+8z=-24 | | 160=8(6x+8) | | 12+5m=50+6m | | u-1/5=2 | | 1-a=6 | | r+5/2=5 | | 5x+10+58+11x+2=58 | | 13=12+t/2 | | 2/3(z)=9 | | -4x+3x-20=0 | | -1=c/4+2 | | 4d-8=6d | | (7y−1)8= | | -5(4+s)=5 | | -3.8x-5.9x=223.1 |